Trajectory Tracking Control System Design For Autonomous Two-Wheeled Robot - Nur Uddin (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
A trajectory tracking control system design of an autonomous two-wheeled robot (TWR) is presented. A TWR has two movements: translation (moving forward/backward) and rotation (turning to the right/left) which are commonly represented by a non-linear kinematic equations. The objective of the trajectory tracking control system is to steer the TWR move on a desired trajectory in planar space. In order to simplify the trajectory tracking control system design, the non-linear kinematic equations were approximated by linear kinematic equations through a linearization. Linear quadratics regulator (LQR) method was applied to design the control system. Computer simulations were done to evaluation performance of the designed control system. The simulation results show that the designed control system was able to make the TWR track a desired trajectory that located 1.4 meter away from the TWR initial position within 3 seconds.